Temperature-humidity regime in the operation of the roofs of historic buildings - Semko, Oleksandr; Filonenko, Olena; Hasenko, Lina; Mahas, Nataliia; Rudenko, Viktor (Academic journal Industrial Machine Building Civil Engineering, 2022)
The article presents the experience of developing engineering solutions for the restoration and preservation of cold pitched attic structures on the example of a historic building in Poltava. A preliminary design solution for the thermal modernization of the attic floor was analyzed, which included the placement of mineral wool insulation in the attic in accordance with requirements of DBN V.2.6-31:2016 with a thickness of 250 mm. Increasing the thickness of the insulation to modern requirements for energy efficiency on a reinforced concrete floor could lead to a decrease in the temperature in the attic, which, in turn, would not contribute to the melting of snow on the roof, which occurred in the last 70 years of the building's operation. A possible increase in snow load along with cooling of the steel truss elements to -20°C can cause brittle fracture of truss elements made of boiling steel. The thickness of the insulation along the attic floor should be taken no more than 100 mm in order to reduce transmission heat losses and maintain a positive temperature in the attic space.
Keywords: attic floor; insulation; temperature and humidity conditions